Optimalisasi Potensi Anak ADHD di Sekolah Dasar melalui Pembelajaran Terstruktur dan Multisensori - Lilik Noeraini; Liftiah Liftiah; Ali Formen (Universitas Muhammadiyah Metro, 2026)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often experience difficulties in maintaining attention, regulating behavior, and achieving optimal learning outcomes in elementary school settings. These challenges require adaptive instructional strategies that are structured, engaging, and responsive to students’ individual needs. This study aimed to analyze the characteristics and learning needs of a student with ADHD and to examine the implementation of structured and multisensory learning approaches in improving focus, behavior, and basic academic outcomes. A descriptive qualitative approach supported by simple quantitative pre-test and post-test data was employed. The study used a case study design involving one second-grade student at SDN 2 Temengeng who was identified as showing ADHD characteristics based on classroom observation and teacher interviews. Data were collected through observation, interviews, documentation, behavioral observation sheets, learning progress notes, and pre-test–post-test assessment. Data validity was strengthened through source and technique triangulation, while qualitative data were analyzed using data reduction, data display, and conclusion drawing. The findings revealed that the student showed core ADHD characteristics, including inattention, hyperactivity, and impulsivity, which affected classroom engagement and academic performance. After the implementation of structured and multisensory learning, the student demonstrated improved attention span, reduced hyperactive and impulsive behaviors, and better basic reading and writing performance. The N-Gain results in the moderate category further indicated that the intervention had meaningful effectiveness. These findings suggest that the integration of structured instruction, clear routines, positive reinforcement, visual media, movement-based activities, and multisensory stimulation can optimize the learning potential of children with ADHD. This study provides practical implications for elementary teachers, parents, and schools in developing adaptive and inclusive learning strategies for students with ADHD.